2022
DOI: 10.3389/fmicb.2022.920618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tree Composition and Soil Depth on Structure and Functionality of Belowground Microbial Communities in Temperate European Forests

Abstract: Depending on their tree species composition, forests recruit different soil microbial communities. Likewise, the vertical nutrient gradient along soil profiles impacts these communities and their activities. In forest soils, bacteria and fungi commonly compete, coexist, and interact, which is challenging for understanding the complex mechanisms behind microbial structuring. Using amplicon sequencing, we analyzed bacterial and fungal diversity in relation to forest composition and soil depth. Moreover, employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…Furthermore, the plastic tarp, initially installed to prevent the growth of weeds that introduce other mycorrhizal types, may have inhibited some processes in nutrient cycling, such as accumulation of organic matter through litter fall and its direct interaction with soil organisms (Berg & McClaugherty, 2014). Plants usually modulate their belowground microbiome partly through the quality and composition of litter (Pollierer et al ., 2007; Prada‐Salcedo et al ., 2022). Therefore, we may expect that species richness effects could be more pronounced in case of direct litter input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the plastic tarp, initially installed to prevent the growth of weeds that introduce other mycorrhizal types, may have inhibited some processes in nutrient cycling, such as accumulation of organic matter through litter fall and its direct interaction with soil organisms (Berg & McClaugherty, 2014). Plants usually modulate their belowground microbiome partly through the quality and composition of litter (Pollierer et al ., 2007; Prada‐Salcedo et al ., 2022). Therefore, we may expect that species richness effects could be more pronounced in case of direct litter input.…”
Section: Discussionmentioning
confidence: 99%
“…New Phytologist (2024) 242: 1614-1629 www.newphytologist.com Ó 2024 The Authors New Phytologist Ó 2024 New Phytologist Foundation through litter fall and its direct interaction with soil organisms (Berg & McClaugherty, 2014). Plants usually modulate their belowground microbiome partly through the quality and composition of litter (Pollierer et al, 2007;Prada-Salcedo et al, 2022). Therefore, we may expect that species richness effects could be more pronounced in case of direct litter input.…”
Section: Source Of Variation Df Ddfmentioning
confidence: 99%
“…Furthermore, the plastic tarp, initially installed to prevent the growth of weeds that introduce other mycorrhizal types, may have inhibited some processes in nutrient cycling, such as accumulation of organic matter through litter fall and its direct interaction with soil organisms (Berg & McClaugherty, 2014). For example, plants usually modulate their belowground microbiome partly through the quality and composition of litter (Pollierer et al ., 2007; Prada-Salcedo et al ., 2022). Therefore, we expect that species richness effects would be more pronounced in case of direct litter input.…”
Section: Discussionmentioning
confidence: 99%
“…In the fungal community, there was no signi cant trend in the various indicators, and the results of measurements at different soil depths were similar. One possible reason is that soil depth primarily shaped bacterial communities, while plant species structure in uenced fungi [44]. Former studies showed that the predicted bacterial diversity in the topsoil was higher than in the corresponding subsoil [30].…”
Section: Differences Among Layers Of Soil Microbial Communitiesmentioning
confidence: 99%